2019
DOI: 10.1158/0008-5472.can-18-2331
|View full text |Cite
|
Sign up to set email alerts
|

MITF Expression Predicts Therapeutic Vulnerability to p300 Inhibition in Human Melanoma

Abstract: Histone modifications, largely regulated by histone acetyltransferases (HAT) and histone deacetylases, have been recognized as major regulatory mechanisms governing human diseases, including cancer. Despite significant effort and recent advances, the mechanism by which the HAT and transcriptional coactivator p300 mediates tumorigenesis remains unclear. Here, we use a genetic and chemical approach to identify the microphthalmia-associated transcription factor (MITF) as a critical downstream target of p300 drivi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 61 publications
(70 reference statements)
5
46
0
Order By: Relevance
“…Kim et al proposed that suppression of p300 acetyltransferase activity with the help of a catalytic p300/CBP inhibitor exhibited effective growth inhibitory effects in melanoma cells. 26 Functional rescue experiments in our study further validated that the CBP/P300-specific activator CTPB promoted EdU-positive cells and reduced apoptosis in the presence of siCCNB1. Lastly, GSEA in the present study disclosed that p53 pathway was significantly conversely regulated in CSCC.…”
Section: Discussionsupporting
confidence: 66%
“…Kim et al proposed that suppression of p300 acetyltransferase activity with the help of a catalytic p300/CBP inhibitor exhibited effective growth inhibitory effects in melanoma cells. 26 Functional rescue experiments in our study further validated that the CBP/P300-specific activator CTPB promoted EdU-positive cells and reduced apoptosis in the presence of siCCNB1. Lastly, GSEA in the present study disclosed that p53 pathway was significantly conversely regulated in CSCC.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies showed that increased ADCY expression generated resistance to MAPK inhibitions and up regulates MITF in melanoma cells 8 , and the suppression of MITF expression by the CH6868398 agent caused melanoma cell growth inhibition 45 . Inhibition of p300 acetyltransferase transcriptional coactivator of MITF by p300/CBP complex had growth inhibitory effects in melanoma cells expressing MITF 46 , 47 , and Kazinol U reduced melanogenesis by inhibition of MITF in melanoma cells 48 . Since response to new agents depends on ADCY3 and MITF expressions, it is possible that patients with distinct genotypes of these genes present differentiated responses to therapies.…”
Section: Discussionmentioning
confidence: 98%
“…In this study both dogs had MITF amplification and the Sheepdog had a CDKN2A deletion and a BRAF amplification and thus considered as a potential driver in this study. MITF activity has been linked to acquired resistance to MAPK inhibitors [ 92 ] and thus it is predicted that MAPK inhibitors will be ineffective in tumors with MITF amplification. MITF is a downstream target of EP300 , a histone acetyltransferase and an oncogene in a subset of melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…There are no current MITF targeted therapies. Instead EP300 targeted therapy have shown potential in preclinical models of MITF overexpressing melanomas [ 92 ]. EP300 therapy may have been effective in the metastatic lesion of the Sheepdog with MITF and EP300 amplification.…”
Section: Discussionmentioning
confidence: 99%